Problem of the Week

Updated at Jun 3, 2019 1:28 PM

This week we have another equation problem:

How would you solve the equation \(2({t}^{2}+6)+2=46\)?

Let's start!



\[2({t}^{2}+6)+2=46\]

1
Subtract \(2\) from both sides.
\[2({t}^{2}+6)=46-2\]

2
Simplify \(46-2\) to \(44\).
\[2({t}^{2}+6)=44\]

3
Divide both sides by \(2\).
\[{t}^{2}+6=\frac{44}{2}\]

4
Simplify \(\frac{44}{2}\) to \(22\).
\[{t}^{2}+6=22\]

5
Subtract \(6\) from both sides.
\[{t}^{2}=22-6\]

6
Simplify \(22-6\) to \(16\).
\[{t}^{2}=16\]

7
Take the square root of both sides.
\[t=\pm \sqrt{16}\]

8
Since \(4\times 4=16\), the square root of \(16\) is \(4\).
\[t=\pm 4\]

Done